Mathematical Modelling and Numerical Simulation of Transmission Dynamics of COVID-19 Pandemic - SOME, Windjiré; LAMIEN, Kassiénou; SO, Ousséni; SOME, Blaise (International Journal of Applied Mathematical Research, 2022)
In this paper we have conceived an original deterministic model for the propagation of Covid-19 dynamics. Mathematical analysis of the model has been done and reveals the existence of a single disease-free equilibrium witch is locally and asymptotically stable. The basic reproduction number  has also been evaluated and gives an idea on the disease evolution in the world. This is because if , the disease disappears whereas if , the disease remains in the population. Numerical results are consistent with the theoretical results and highlight the effect of the infectious contact rate α on the evolution of the pandemic.